MAKNA PERILAKU JUJUR BERANI JUJUR ITU HEBAT: DALAM AKTIVITAS AKADEMIK - , Ernayanti Nur Widhi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dishonest behavior in academic activity often becomes the news in mass media in Indonesia both in printed and in electronic media. However, in the middle of this condition, there are students who still have commitment to behave honestly in their academic activity. Staats, Hupp, dan Hagley (2008) explain that honest behavior that is performed by students becomes a form of heroic attitude that contains the character of bravery and readiness as well as the willingness to take the risk. These research objectives are to explore, to understand, and to explain the meaning of academic honesty. The main focuses of the research is the perspective, meaningfulness, and subjective view of senior high school students which correlates with honest behavior in academic activities. The participants of the research were five students of senior high school grade XI. The approach used is phenomenological qualitative. Data collection was conducted by having semi structured depth interview. Data analysis was done by organizing the data, reading the whole data to get general impression, to analyze the detail through coding process, and to present description and theme in quantitative narration. The result of the research covers the incoming of several themes, both unique and general theme, as well as the meaning of performing honest behavior. Academic responsibility and self representation become the meaning of honest behavior that was performed by students in senior high school. By using planned behavior theory, it can be determined that subjective norm existing inside the studentsâ character has significant roles in the process of choosing hones and dishonest behavior. Subjective norm existing in studentsâ character is honest behavior that must be important thing that must be struggled. Being honest is definitely right. Dishonest behavior causes sin. Dishonest behavior is the form of friendship